PROVISION OF INFRARED THERAPY AND ACUPRESSURE THERAPY TO REDUCE JOINT PAIN IN GUE VILLAGE - Putra, Yadi; Fauziah; Ismail (Transpublika Publisher, 2022)
Joint pain is a prevalent disease among the elderly, and treatment can be carried out through pharmacological and non-pharmacological methods. Infrared and acupressure therapies are two effective solutions to alleviate this problem. In this community service, we utilized infrared therapy and acupressure therapy to reduce joint pain. A quasi-experimental study with a control group pretest-posttest design was conducted, and the therapy was administered five times. The activity took place on June 29, 2022, in Gue Village, Kuta Baro District, Aceh Besar, and was facilitated by D3 Nursing lecturers with the assistance of students. The study's findings indicate a decrease in the pain scale from an average of 5.30% before therapy to 2.40% after therapy among 20 elderly patients. This therapy can be imparted to health cadres in the community and is a viable option for managing joint pain.